Fire/life safety in theatres - Kwon, Jaewook (Knovel, 2012)
Stage fire protection measures have been established, codified and enforced throughout the world and have changed little over the past 100 years. Technological advancements in both stagecraft and fire protection systems have led to a need in the theater community to study the current state of theater fire protection requirements. The objective of this study was to assess the level of protection afforded by stage active fire protection measures, as prescribed by the International Building Code (IBC) and NFPA 80 Standard for Fire Doors and Other Opening Protectives.
Knovel brief article.
Keywords: Theaters -- Fires and fire prevention.; Fire protection engineering.; Fire prevention.; elektronické knihy; electronic books